2020
DOI: 10.1016/s2665-9913(20)30173-9
|View full text |Cite|
|
Sign up to set email alerts
|

Tocilizumab in patients with severe COVID-19: a retrospective cohort study

Abstract: Background No therapy is approved for COVID-19 pneumonia. The aim of this study was to assess the role of tocilizumab in reducing the risk of invasive mechanical ventilation and death in patients with severe COVID-19 pneumonia who received standard of care treatment.Methods This retrospective, observational cohort study included adults (≥18 years) with severe COVID-19 pneumonia who were admitted to tertiary care centres in Bologna and Reggio Emilia, Italy, between Feb 21 and March 24, 2020, and a tertiary care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
953
8
47

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 899 publications
(1,078 citation statements)
references
References 35 publications
40
953
8
47
Order By: Relevance
“…Campochiaro et al found no signi cant difference in 28-day mortality (15% vs. 22%, p = 0.15) whereas Somers et al identi ed a 45% reduction in the risk of death (aHR 0.55, 95% CI 0.33-0.90) in mechanically ventilated patients [14,25]. Guaraldi et al also found tocilizumab to be associated with a reduced risk of all-cause mortality after adjusting for age, sex, recruiting center, duration of symptoms, and SOFA score (aHR 0.38, 95% CI 0.17-0.83) [15]. Overall, these ndings suggest a possile mortality bene t with tocilizumab, however it is important to recognize that many patients also received steroids, which has been independently associated with improved survival [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Campochiaro et al found no signi cant difference in 28-day mortality (15% vs. 22%, p = 0.15) whereas Somers et al identi ed a 45% reduction in the risk of death (aHR 0.55, 95% CI 0.33-0.90) in mechanically ventilated patients [14,25]. Guaraldi et al also found tocilizumab to be associated with a reduced risk of all-cause mortality after adjusting for age, sex, recruiting center, duration of symptoms, and SOFA score (aHR 0.38, 95% CI 0.17-0.83) [15]. Overall, these ndings suggest a possile mortality bene t with tocilizumab, however it is important to recognize that many patients also received steroids, which has been independently associated with improved survival [27].…”
Section: Discussionmentioning
confidence: 99%
“…[8]. Limited observational studies have demonstrated tocilizumab to be associated with improvements in in ammatory markers, clinical response, and survival [9][10][11][12][13][14][15][16]. During an unprecedented time when proven effective therapies remain lacking, we aimed to describe our experience using off-label tocilizumab for COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Recently it has been associated with improved survival in patients with severe COVID-19 pneumonia with evidence of CRS. 15,16 In general tocilizumab is well tolerated but can induce neutropenia, and an increased risk of developing infections has been reported. 17,18 Furthermore, it may predispose to a delay in detecting active infection because of the masking effect of a suppressed C reactive protein (CRP) response.…”
Section: Resultsmentioning
confidence: 99%
“…This dysregulation is characterized by high production of proin ammatory cytokines by monocytes and macrophages and CD4 lymphocyte depletion that contributes to the progression of in ammation of lung parenchyma [19]. The direct role of IL-6 in Covid-19 pathogenesis is further supported by ndings that IL-6 inhibition improves the prognosis of severe Covid-19 [27,25].…”
Section: Discussionmentioning
confidence: 96%